Análisis exhaustivo de los Fondos de Inversión: una investigación empírica: El caso Colombiano - Montoya Moreno, Iván Andrés (IE University, 2020)
This study uses the most comprehensive dataset ever prepared to study investment fund performance in Colombia in terms of both number of funds and number of attributes. In the Colombian market, we empirically study i) the performance of investment funds and the style classification, ii) the link between management fees and performance among investment funds, and iii) the factors that may explain the differences in performance across these funds. We seek to understand whether i) investors have the right information to evaluate fund performance and ii) investment advisor compensation is determined according to the level of performance or some other set of determinants. We provide useful benchmarks for evaluating relative past performance, and the methodology employed is a useful descriptor of fund styles and performance. We find that investment funds adopt styles that do not deviate markedly from passive benchmarks and that few take significant positions away from the index. We provide evidence that the local classification provided either by the company advisory or even by the regulator has relatively little power in explaining differential fund performance. No evidence exists that argues that advisory companies in Colombia intentionally present higher alphas that result in more value added. However, we realize that all of the information that provides a consistent view of investment decisions in Colombia needs to be systematically collected by the regulator. We provide new evidence on products offered by company advisors in this market. In particular, our results on the distribution of fund styles suggest that overall investment funds tilt toward money market investing, which might be a reason that, historically and on average, funds cannot beat the market after costs. From the standpoint of an investor, drifts in style with poor past performance introduce variability that deserves monitoring. Our empirical evidence extends the current finance literature for non-U.S. funds because we find a positive relationship between fees and performance. Relatively sophisticated investors in Colombia appear to penalize funds for poor performance. The elasticity of demand or performance sensitivity for investment funds in Colombia seems to influence the determinant of fees. In our investigation, we encountered common determinants of investment funds¿ performance according to previous research but also found some important differences. This analysis will also help governments and regulators formulate their policies because the effect of incentives on riskadjusted performance should have important policy implications.
A Comprehensive Analysis of Investment Funds: An empirical investigation – The Colombian case
Keywords: Investment funds; Fund´s fee compensation; Fund Performance; Management Style and Style analysis; Teoría de la Inversión; Consumo, Ahorro, Inversión; Finanzas y Seguros; Inversión Exterior